Myeloid-Derived Suppressor Cells in Multiple Myeloma: Pre-Clinical Research and Translational Opportunities - Botta, Cirino; Gullà, Annamaria; Correale, Pierpaolo; Tagliaferri, Pierosandro; Tassone, Pierfrancesco (Frontiers in Oncology, 2014)
Immunosuppressive cells have been reported to play an important role in tumor progression mainly because of their capability to promote immune-escape, angiogenesis and metastasis. Among them, myeloid derived suppressor cells (MDSCs) have been recently identified as immature myeloid cells, induced by tumor-associated inflammation, able to impair both innate and adaptive immunity. While murine MDSCs are usually identified by the expression of CD11b and Gr-1, human MDSCs represent a more heterogeneous population characterized by the expression of CD33 and CD11b, low or no HLA-DR and variable CD14 and CD15. In particular, the last two may alternatively identify monocyte-like or granulocyte-like MDSC subsets with different immunosuppressive properties. Recently, a substantial increase of MDSCs has been found in peripheral blood and bone marrow (BM) of multiple myeloma (MM) patients with a role in disease progression and/or drug resistance. Preclinical models recapitulating the complexity of the MM-related BM microenvironment (BMM) are major tools for the study of the interactions between MM cells and cells of the BMM (including MDSCs) and for the development of new agents targeting MM-associated immune suppressive cells. This review will focus on current strategies for human MDSCs generation and investigation of their immunosuppressive function in vitro and in vivo, taking into account the relevant relationship occurring within the MM-BMM. We will then provide trends in MDSC-associated research and suggest potential application for the treatment of MM.